PENGARUH PENYELESAIAN KLAIM ASURANSI TERHADAP PENCAPAIAN TARGET PENJUALAN PRODUK ASURANSI AJB BUMIPUTERA 1912 CABANG BENGKULU - Handayani, Sri (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2017)
Sri Handayani; Insurance claims are the demands of the insured party in connection with the contract between the insurer with the insured person that each of the parties bind themselves to guarantee the payment of compensation by penaggung if insurance premium payments have been made by the insured party, when the disaster suffered by the insured person. This study aimed to examine the effect of the settlement of insurance claims against insurance product sales target AJB BUMIPUTERA 1912 Cabang Bengkulu. The sample in this study is the settlement of insurance claims and insurance product sales target AJB BUMIPUTERA 1912 Cabang bengkulu observation period of 5 years. The method used is the correlation coefficient. These results indicate that a growing number of insurance claims are settled, the higher the achievement of sales of insurance products offered AJB BUMIPUTERA 1912 cabang Bengkulu.Key words: Insurance claims